Razredniki in vključevanje marginaliziranih skupin učencev v oddelčno skupnost - Anja Smole; Tina Tina Vršnik Perše (Journal of Elementary Education, 2018)
Class teachers and inclusion of marginalized groups of pupils in the class. In the first part of the article, we present the characteristics of marginalized groups of pupils and the role of the class teacher in integrating them into the class. The experimental part reports the results of the study, which included 381class teachers from Slovenian elementary schools. Through this research, we sought to establish whether the statistics show characteristic differences in selfassessment of the qualification for working with marginalized groups of pupils; differences in the quantity of knowledge about integration of marginalized groups gained through education; differences in the quantity of experience in integrating marginalized groups of pupils; and differences in the quantity of additional work with integration of marginalized groups of pupils into theclassroom, based on years of service, town size and educational level of the class teachers.We researched the difficulty of including various marginalized groups into classes. We also tried to find out the opinions of class teachers on the success of integration strategies for these groups of pupils in the classroom.DOI: 10.18690/rei.11.3.233 -250.2018COBISS-ID: 24275976